Enzymatic degumming of silk with microbial proteases - More, Shivaji V.; Khandelwal, Harish B.; Joseph, M. A.; Laxman, Ryali Seeta (Journal of Natural Fibers, 2013)
Degumming of Chinese bivoltine silk with alkaline proteases from various microbial sources was investigated and compared with commercial enzymes. Among the proteases tested, two fungal and two actinomycete proteases were promising, which showed weight loss similar to conventional method (19.58% to 21.78%). Conidiobolus brefeldianus and BOA-2 proteases were best enzymes, which showed weight loss similar to conventional method with low enzyme concentrations and in shorter time. No significant differences were found in tensile strength or elongation at break by enzymatic degumming indicating that there was no damage to the fiber. Scanning electron micrographs showed the sericin deposits were removed and the fibers were separated.
Keywords: Alkaline Protease; bivoltine; degumming; microbial; Silk; weight loss